The Role of Leadership Style in Building a Discipline Culture in Pesantren: Facing the Challenges of Social and Technological Change - Al Laisty, M. Dikhyah; Darmawan, Didit; Fajar, Abbas Sofwan Matlail (Bulletin of Science, Technology and Society, 2024)
This study aims to analyze the influence of leadership styles applied in pesantren on the implementation of a culture of discipline among santri (pesantren students) and the challenges faced by pesantren in maintaining a culture of discipline amid social and technological developments. Pesantren as religious educational institutions have characteristics that prioritize discipline as a basic value. The leadership style applied by the pesantren leader, whether authoritarian or democratic, can influence the extent to which discipline is applied in the life of the santri. However, increasingly open social change and the rapid development of technology, especially in terms of the use of social media, are a major challenge to maintaining a culture of discipline. The uncontrolled use of technology often disrupts the concentration and focus of santri, while changes in the mindset of the younger generation, who are more open to freedom, also risk reducing the level of discipline. This study shows that pesantren must be able to adapt their leadership style to the times, without sacrificing the values of discipline that have long been the basis of pesantren life. Therefore, a more flexible approach is needed to manage technology and foster relationships between pesantren leaders and students. In conclusion, discipline management in pesantren requires a balance between firmness and an approach that prioritizes humanitarian values and adaptation to the challenges of the times.